Wet jet milling for solid state batteries

CN122968385APending Publication Date: 2026-10-23FORD GLOBAL TECH LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610367337.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-07
Filing Date
2026-03-24
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

虽然总体处理装备和方法保持类似,但是由于硫化物基固体电解质的化学稳定性,S-SSLB制造需要不同的溶剂和粘结剂

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968385A_ABST
    Figure CN122968385A_ABST
Patent Text Reader

Abstract

The present disclosure provides "Wet Jet Milling for Solid State Batteries". A sulfide-based solid state lithium-ion battery is presented. The sulfide-based solid state lithium-ion battery includes a negative electrode, a positive electrode, and a separator positioned between the electrodes. The positive electrode includes active material particles having insoluble polymer binder molecules adhered to the surface of the active material particles. These binder molecules are configured to sterically hinder adjacent active material particles, thereby reducing particle aggregation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to wet jet milling for solid-state batteries. Background Technology

[0002] The manufacture of sulfide-based solid-state lithium-ion batteries (S-SSLBs) can include conventional wet slurry mixing and coating techniques used in lithium-ion battery production. This approach allows for the potential retrofitting of existing Gigafactories to produce S-SSLBs. While the overall processing equipment and methods remain similar, S-SSLB manufacturing requires different solvents and binders due to the chemical stability of sulfide-based solid electrolytes. Summary of the Invention

[0003] A sulfide-based solid-state lithium-ion battery is provided. The battery includes: a negative electrode; a positive electrode having insoluble polymer binder molecules that adhere to the surface of positive electrode active material particles and are configured to spatially impede adjacent positive electrode active materials; and a separator between the negative electrode and the positive electrode. The polymer binder may be selected from the group consisting of polyvinylidene fluoride, polyacrylonitrile, carboxymethyl cellulose, polyimide, and styrene-butadiene rubber. The positive electrode may include a lithium metal oxide selected from the group consisting of lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, lithium manganese oxide, and lithium iron phosphate. The positive electrode may also include a carbonaceous conductive additive. The positive electrode active material particles may have an average particle size between 1 μm and 10 μm. The polymer binder may be present in an amount of 1% to 5% by weight relative to the solid electrolyte.

[0004] A method for forming an electrode for a solid-state lithium-ion battery is provided. The method includes pressurizing a slurry of polymer binder molecules and positive electrode active material from a slurry tank via an intensifier to form a pressurized slurry; then wet-jetting the pressurized slurry in a grinding chamber to disperse the polymer binder onto the surface of the positive electrode active material particles and form a stable dispersion; and coating the stable dispersion onto a substrate to form an electrode. The intensifier can increase the pressure of the slurry to at least 200 MPa. The polymer binder in the slurry may be insoluble in a solvent. The pressurized slurry can be released at an inclined angle into the wet-jetting chamber. The wet-jetting chamber can be configured to reduce agglomeration of the positive electrode active material particles. The substrate may be an aluminum foil. The coated substrate can be calendered. Before coating onto the substrate, the stable dispersion can be filtered to remove particles larger than 10 μm.

[0005] A fabrication system for solid-state lithium-ion electrodes is provided. The system includes: an intensifier fluidly coupled to a slurry tank via a pump; a wet blast milling chamber configured to pulverize the slurry from the intensifier and induce a stable dispersion of a polymer binder onto the surface of active material particles; and a coater configured to coat the stable dispersion from the wet blast milling chamber onto a substrate. The intensifier may be a hydraulic intensifier. The coater may include a slit coater. The slurry tank may be configured to maintain a continuous slurry flow to the intensifier. A filter may be disposed between the wet blast milling chamber and the coater to remove particles larger than 10 μm. The coater may be configured to coat the stable dispersion onto a moving substrate. Attached Figure Description

[0006] Figure 1 This is a schematic diagram of a cross-section of a sulfide-based solid-state lithium-ion battery.

[0007] Figure 2 It is a fabrication system for forming solid-state positive electrodes; and

[0008] Figure 3 This is a flowchart of a method for preparing solid-state electrodes. Detailed Implementation

[0009] This document describes embodiments. However, it should be understood that the disclosed embodiments are merely examples and other embodiments may take different and alternative forms. The drawings are not necessarily drawn to scale. Some features may be enlarged or minimized to show details of specific components. Therefore, the specific structural and functional details disclosed herein should not be construed as limiting, but merely as a representative basis for teaching those skilled in the art.

[0010] Various features shown and described with reference to any of the accompanying drawings may be combined with features shown in one or more other drawings to produce embodiments not explicitly shown or described. The combinations of features shown provide representative embodiments for typical applications. However, for a particular application or implementation, various combinations and modifications of features consistent with the teachings of this disclosure may be desired.

[0011] Unless otherwise expressly stated, the terminology used in this disclosure should be interpreted broadly and inclusively. Unless the context otherwise requires, singular terms such as “an,” “a,” and “the” encompass plural indicators. Similarly, unless otherwise stated, references to percentages, parts, and ratios should be understood as by weight. Ranges include all intermediate values ​​and subranges within their boundaries. For example, a pressure range of 200 MPa to 3000 MPa includes specific values ​​such as 500 MPa, 1500 MPa, and 2700 MPa. Unless otherwise expressly stated, all numerical values ​​and ranges in this document are prefixed with the term “about.” This applies even if “about” is not explicitly stated.

[0012] The term "dispersion" refers to a mixture in which the polymer binder, cathode active material particles, and a solvent in which the polymer binder remains insoluble. "Stable dispersion" refers to a dispersion that resists sedimentation over an extended period of time, such as a week or longer. The term "wet jet milling" refers to a high-pressure mechanical process that physically and chemically attaches the polymer binder to the surface of the cathode active material particles.

[0013] As used herein, “polymer binder” encompasses a range of polymeric materials capable of physically and chemically adhering to cathode active material particles during wet blasting. Examples include, but are not limited to, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), carboxymethyl cellulose (CMC), polyimide (PI), and styrene-butadiene rubber (SBR).

[0014] The term "cathode active material particles" refers to particles used as active materials in the cathode of lithium-ion batteries, including lithium metal oxides such as lithium nickel manganese cobalt oxide (NMC), lithium nickel cobalt aluminum oxide (NCA), lithium cobalt oxide oxide (LCO), lithium manganese oxide (LMO), and lithium iron phosphate (LFP). The median diameter of the particles typically ranges from 1 µm to 20 µm.

[0015] The reference to "non-θ solvent" indicates a solvent in which the polymer binder remains insoluble during the blending process. Examples include water, alcohols, ketones, esters, ethers, and mixtures thereof. The solvent serves as a medium for dispersing the particles but does not promote polymer dissolution.

[0016] The term "steric hindrance" describes the spatial separation between particles in a stable dispersion caused by polymer chains adhering to the particle surface. This steric effect maintains particle dispersion within the solvent, thereby preventing aggregation and sedimentation.

[0017] This disclosure relates to a method for manufacturing S-SSLBs that represents an advancement over conventional wet slurry mixing and coating techniques. While conventional processes rely on dissolving the polymer binder in a processing solvent prior to the introduction of active material particles, this approach typically results in uneven binder distribution, polymer-rich regions, and electrochemically inactive voids. The method disclosed herein utilizes wet jet milling to achieve precise polymer adhesion and uniform particle dispersion, thereby enhancing the electrochemical and mechanical properties of the resulting electrode.

[0018] Steric effects prevent agglomeration and sedimentation, thereby maintaining the homogeneity of the dispersion. Conventional methods lack control over binder placement, leading to impaired particle connectivity, increased tortuosity of ion transport, and reduced electrochemical performance. In contrast, the disclosed method involves blending an undissolved polymer binder with cathode active material particles and a solvent to form an intentionally unstable dispersion. This dispersion is then stabilized by wet jet milling, which applies strong shear forces to physically and chemically attach the polymer chains to the particle surface. This attachment creates steric hindrance, thereby maintaining uniform dispersion and preventing sedimentation. This technique allows for reduced binder usage while maintaining mechanical integrity and electrochemical performance.

[0019] The advantage of wet jet milling lies in its flexibility in selecting processing solvents. Unlike conventional methods that rely on specific solvents (such as n-methylpyrrolidone (NMP)) to dissolve the polymer binder, this method is adaptable to a wide range of solvents, including those that are not highly volatile. The choice of solvent is based on its compatibility with the cathode active material and its ability to maintain the polymer binder in an undissolved state during dispersion formation.

[0020] The process parameters of wet jet milling (including pressure and duration) affect the degree of polymer adhesion. Pressures ranging from 200 bar to 3000 bar, combined with controlled milling durations, allow for precise fine-tuning of polymer coverage on the cathode active material particles. This minimizes the presence of excess polymer, maximizes the active surface area, and reduces electrochemically inactive regions within the electrode structure.

[0021] Wet blast milling is operated by pumping conventional slurry through an intensifier to increase the pressure to a specific level (typically around 200 MPa), which can be hydraulic or other suitable intensifier. Upon entering the wet blast mill chamber, this pressure is rapidly released, subjecting the slurry to intense shear forces. These forces are particularly effective in breaking down secondary particle structures with weak adhesion between primary particles. Furthermore, the process effectively breaks up agglomerates and promotes uniform dispersion, thereby ensuring optimal binder integration.

[0022] The slurry can be filtered through a filter of approximately 10 micrometers (µm) before being pumped to the coater, thereby reducing the likelihood of particle aggregation during deposition. This filtration step ensures a uniform coating and enhances adhesion when applied to the electrode substrate. The disclosed wet jet milling technique provides greater process stability and facilitates precise control over particle size distribution, binder content, and slurry uniformity.

[0023] The disclosed method addresses mechanical integrity challenges by maintaining uniform polymer coverage and increasing cohesion during battery assembly and cycling. Post-processing steps, such as drying and heating, further enhance polymer adhesion and structural stability. These improvements contribute to long-term battery performance and reliability. The process allows for precise design of electrode properties, including polymer loading, particle size distribution, and dispersion stability. These parameters can be adjusted to modify rate capacity, minimize electrolyte breakdown, and improve lithium-ion transport efficiency. The adjusted polymer placement maintains contact between the cathode active material particles and the electrolyte, thereby reducing internal resistance and improving overall performance.

[0024] Furthermore, the disclosed methods are compatible with a variety of cathode active materials, including high energy density compositions such as NMC and NCA. By achieving polymer control and particle dispersion, these techniques improve the electrochemical and mechanical properties of advanced cathode materials. In addition, this reduces the amount of binder used and allows the use of sustainable solvents.

[0025] The disclosed technology extends beyond lithium-ion batteries and can be applied to other energy storage systems that require control of polymer-material interactions. Potential applications include supercapacitors, solid-state batteries, and other electrochemical devices that require uniform material distribution and minimization of inactive regions.

[0026] In one example, wet blast milling supports the use of polymer binders that are insoluble in the processing solvent. The low-polarity solvent facilitates the flow of solid electrolyte particles through the milling process, while the suspended polymer particles remain undissolved. As the polymer particles enter the milling chamber, high pressure forces them to adhere to the ceramic particles, forming a stable dispersion suitable for coating and solid-state lithium-ion battery manufacturing. This technique allows for a wider selection of binders, enabling further reductions in polymer content while maintaining coating strength. In another embodiment, samples of NMC, carbon, and PVDF can be wet blast milled using a non-protic solvent that does not dissolve PVDF, such as ethyl acetate. A uniform coating can be successfully deposited and calendered onto an aluminum foil with sufficient adhesion.

[0027] Figure 1A schematic cross-sectional view of a sulfide-based solid-state lithium-ion battery 10 is shown. The sulfide-based solid-state lithium-ion battery 10 includes a negative electrode 12, a positive electrode 14, and a separator 16 positioned between them. The negative electrode 12 may comprise graphite or other suitable lithium-ion intercalation materials to provide electrochemical functionality during operation of the sulfide-based solid-state lithium-ion battery 10. The separator 16 comprises a thin porous membrane configured to prevent electrical short circuits by physically separating the negative electrode 12 and the positive electrode 14, while allowing ionic conductivity for charge and discharge cycles.

[0028] The positive electrode 14 includes active material particles 18, such as lithium metal oxides, including NMC, NCA, LCO, LMO, or LFP. These active material particles 18 store and release lithium ions for energy storage and delivery. The positive electrode 14 also includes carbonaceous conductive additive particles 20 dispersed within the active material particles 18. These additives establish a conductive network and facilitate the efficient transport of electrons from the active material particles 18 to the battery current collector.

[0029] Insoluble polymer binder molecules 22 adhere to the surface of the active material particles 18 within the positive electrode 14. Suitable polymer binders include PVDF, PAN, CMC, PI, or SBR. These polymer binders 22 maintain mechanical cohesion by physically adhering the active material particles 18 together and to the carbonaceous conductive additive particles 20, thereby preventing separation during repeated charge and discharge cycles. Additionally, the molecules of the polymer binder 22 spatially hinder adjacent active material particles, which allows for increased electrolyte accessibility and facilitates efficient ion transport. The polymer binder 22 may be included in an amount ranging from about 1 wt% to about 5 wt% relative to the solid electrolyte utilized in the sulfide-based solid-state lithium-ion battery 10.

[0030] Figure 2 A fabrication system 24 for manufacturing the positive electrode 14 of a sulfide-based solid-state lithium-ion battery 10 is shown. Initially, a slurry tank 26 stores a slurry 28 comprising polymer binder molecules and positive electrode active material. The slurry 28 is transported from the slurry tank 26 to a pump 30, which further guides the slurry 28 toward a first enhancer 32 and a second enhancer 34. The two enhancers 32, 34 connected in parallel increase the pressure of the slurry 28, thereby forming a pressurized slurry 36.

[0031] The pressurized slurry 36 then enters a wet jet milling chamber 38. Within the wet jet milling chamber 38, polymer binder molecules are dispersed onto the surface of the positive electrode active material particles, thereby producing a stable dispersion 40. The wet jet milling chamber 38 operates by creating shear forces and turbulent conditions by forcing the pressurized slurry 36 through a narrow channel or nozzle under high pressure. These conditions break up agglomerates and uniformly distribute the polymer binder molecules onto the surface of the active material particles. Therefore, the resulting stable dispersion 40 is homogeneous and exhibits increased electrode uniformity.

[0032] The stable dispersion 40 is then passed through a filter 42, which may be selected from filters such as screen filters, membrane filters, or cartridge filters, and is designed to remove excessively large particles or agglomerates and ensure the uniformity and consistency of the dispersion. Filtration produces a filtered stable dispersion 44 with increased homogeneity and particle size uniformity. The filtered stable dispersion 44 is transported to a coater 46, in which the dispersion can be uniformly applied onto a suitable substrate (such as aluminum foil, copper foil, or a flexible polymer substrate, such as polyethylene terephthalate coated with a conductive film) to form a positive electrode 14 in a sulfide-based solid-state lithium-ion battery 10.

[0033] Figure 3 A flowchart of a method 48 for preparing the positive electrode 14 for manufacturing a sulfide-based solid-state lithium-ion battery 10 is shown. The method begins at step 50 by pressurizing a slurry comprising polymer binder molecules and positive electrode active material particles using an intensifier, increasing the slurry pressure to at least about 200 MPa. The slurry originating from the slurry tank contains polymer binder molecules, which may be PVDF, PAN, CMC, PI, or SBR, combined with positive electrode active material particles having an average particle size of about 1 μm to 10 μm.

[0034] In step 52, the slurry is guided through an intensifier, thereby sufficiently increasing the pressure to at least 200 MPa, which helps to break up agglomerates and ensure thorough mixing. Following this, the pressurized slurry enters a wet jet mill chamber, where, under high shear and turbulent conditions, polymer binder molecules are uniformly dispersed onto the surface of the positive electrode active material particles. This process effectively creates a stable dispersion that maintains surface coverage and steric hindrance between adjacent particles to improve ion transport efficiency.

[0035] After formation, the stable dispersion can undergo an optional filtration step to remove particles larger than approximately 10 μm to produce a filtered stable dispersion. This filtration creates uniformity and allows for consistent coating performance. In step 54, the stable dispersion is uniformly coated onto a suitable substrate (such as a metal foil), and may subsequently undergo a calendering process to achieve uniform thickness and increased electrode density. The resulting coated substrate forms a solid-state lithium-ion battery positive electrode ready for battery assembly.

[0036] While exemplary embodiments have been described above, these embodiments are not intended to describe all possible forms covered by the claims. The language used in this specification is descriptive rather than restrictive, and it should be understood that various changes may be made without departing from the spirit and scope of the disclosed material.

[0037] As previously described, features of various embodiments can be combined to form other embodiments that may not be explicitly described or shown in this disclosure. While various embodiments may have been described as offering advantages or preferences over other embodiments or prior art implementations in terms of one or more desired characteristics, those skilled in the art will recognize that one or more features or characteristics can be compromised to achieve desired overall system properties, depending on the specific application and implementation. These properties may include, but are not limited to, strength, durability, marketability, appearance, packaging, size, serviceability, weight, manufacturability, ease of assembly, etc. Therefore, embodiments described as less desirable in terms of one or more characteristics than those desired by other embodiments or prior art implementations are within the scope of this disclosure and may be desirable for a particular application.

[0038] According to the present invention, a sulfide-based solid-state lithium-ion battery is provided, comprising: a negative electrode; a positive electrode having insoluble polymer binder molecules that adhere to the surface of positive electrode active material particles and are configured to spatially impede adjacent positive electrode active materials; and a separator between the negative electrode and the positive electrode.

[0039] According to an embodiment, the polymer binder is selected from the group consisting of polyvinylidene fluoride, polyacrylonitrile, carboxymethyl cellulose, polyimide and styrene-butadiene rubber.

[0040] According to an embodiment, the positive electrode is a lithium metal oxide selected from the group consisting of lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, lithium manganese oxide, and lithium iron phosphate.

[0041] According to an embodiment, the positive electrode includes a carbonaceous conductive additive.

[0042] According to an embodiment, the positive electrode active material particles have an average particle size between 1 μm and 10 μm.

[0043] According to an embodiment, the polymer binder is present in an amount of 1% to 5% by weight relative to the solid electrolyte.

[0044] According to the present invention, a method for forming an electrode for a solid-state lithium-ion battery includes: pressurizing a slurry of polymer binder molecules and positive electrode active material from a slurry tank via an intensifier to form a pressurized slurry; performing wet jet milling on the pressurized slurry to disperse the polymer binder onto the surface of the particles of the positive electrode active material to form a stable dispersion; and coating the stable dispersion onto a substrate to form an electrode.

[0045] In one aspect of the invention, the enhancer increases the pressure of the slurry to at least 200 MPa.

[0046] In one aspect of the invention, the polymer binder in the slurry is insoluble in a solvent.

[0047] In one aspect of the invention, the pressurized slurry is wet-jet milled at an inclined angle.

[0048] In one aspect of the invention, wet jet milling is configured to reduce the agglomeration of the positive electrode active material particles.

[0049] In one aspect of the invention, the substrate is an aluminum foil.

[0050] In one aspect of the invention, the electrode is rolled.

[0051] In one aspect of the invention, the stable dispersion is filtered before being coated onto a substrate to remove particles larger than 10 μm.

[0052] According to the present invention, a fabrication system for a solid-state lithium-ion electrode is provided, comprising: a reinforcing device fluidly connected to a slurry tank via a pump; a wet jet milling chamber configured to pulverize the slurry from the reinforcing device and induce a stable dispersion of a polymer binder onto the surface of active material particles; and a coating device configured to coat the stable dispersion from the wet jet milling chamber onto a substrate.

[0053] According to an embodiment, the enhancer is a hydraulic enhancer.

[0054] According to an embodiment, the applicator includes a slit applicator.

[0055] According to an embodiment, the slurry tank is configured to maintain a continuous slurry flow to the intensifier.

[0056] According to an embodiment, a filter is disposed between the wet jet mill chamber and the applicator to remove particles larger than 10 μm.

[0057] According to an embodiment, the applicator is configured to apply the stable dispersion onto a moving substrate.

Claims

1. A sulfide-based solid-state lithium-ion battery, comprising: negative electrode; A positive electrode having insoluble polymer binder molecules that adhere to the surface of positive electrode active material particles and are configured to spatially hinder adjacent positive electrode active materials. as well as A diaphragm is provided between the negative electrode and the positive electrode.

2. The sulfide-based solid-state lithium-ion battery of claim 1, wherein the polymer binder is selected from the group consisting of polyvinylidene fluoride, polyacrylonitrile, carboxymethyl cellulose, polyimide and styrene-butadiene rubber.

3. The sulfide-based solid-state lithium-ion battery of claim 1, wherein the positive electrode is a lithium metal oxide selected from the group consisting of lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, lithium manganese oxide and lithium iron phosphate.

4. The sulfide-based solid-state lithium-ion battery of claim 1, wherein the positive electrode comprises a carbonaceous conductive additive.

5. The sulfide-based solid-state lithium-ion battery of claim 1, wherein the positive electrode active material particles have an average particle size between 1 μm and 10 μm.

6. The sulfide-based solid-state lithium-ion battery of claim 1, wherein the polymer binder is present in an amount of 1% to 5% by weight relative to the solid electrolyte.

7. A method for forming an electrode for a solid-state lithium-ion battery, comprising: A pressurized slurry is formed by pressurizing a slurry containing polymer binder molecules and positive electrode active material from a slurry tank via an intensifier. The pressurized slurry is subjected to wet jet milling to disperse the polymer binder onto the surface of the positive electrode active material particles to form a stable dispersion; as well as The stable dispersion is coated onto a substrate to form an electrode.

8. The method of claim 7, wherein the enhancer increases the pressure of the slurry to at least 200 MPa.

9. The method of claim 7, wherein the polymer binder in the slurry is insoluble in a solvent.

10. The method of claim 7, wherein the pressurized slurry is wet-jet milled at an inclined angle.

11. The method of claim 7, wherein wet jet milling is configured to reduce the agglomeration of the positive electrode active material particles.

12. The method of claim 7, wherein the substrate is an aluminum foil.

13. The method of claim 7, wherein the electrode is rolled.

14. The method of claim 7, wherein the stable dispersion is filtered to remove particles larger than 10 μm before being coated onto the substrate.

15. A system for fabricating a solid-state lithium-ion electrode, comprising: The enhancer is fluidly connected to the slurry tank via a pump; A wet jet milling chamber configured to pulverize slurry from the reinforcing unit and induce a stable dispersion of polymer binder onto the surface of active material particles; as well as A coating apparatus configured to apply the stable dispersion from the wet jet mill chamber onto a substrate.